Consumption Trends During the COVID-19 Crisis: How Awe, Coping, and Social Norms Drive Utilitarian Purchases - Yang, Yikai; Li, Ou; Peng, Xixian; Wang, Lei (Frontiers in Psychology, 2020)
As the coronavirus disease 2019 (COVID-19) crisis continues to worsen globally, there exists a widespread enthusiasm for buying utilitarian products in the retail market, irrespective of culture or nationality. However, the questions of whether and why being involved in a public health emergency like the COVID-19 crisis could modify consumer behaviors have been underexplored by previous literature. Drawing on the theory of awe that highlights the important role in influencing human behaviors when they are facing unexpected events that transcends the frame of existing references, the present research aims to clarify the relationship between COVID-19 involvement and consumer preference for utilitarian versus hedonic products. We collected data from 512 Chinese participants (319 women; average age 29.11 years [SD = 11.89]) during the outbreak of COVID-19. The results of structural equation modeling showed that COVID-19 involvement was positively related to the preference for utilitarian products (vs. hedonic products). More importantly, this relationship could be explained via the mediated effects of awe, problem-focused coping, and social norm compliance. The present research emphasizes the non-negligible role of public health emergencies in modifying consumer behavior and the role of awe in explaining the psychological influence of public health emergencies.